Blood flow in artificial bypass graft: A numerical study - L. C. Sousa (2011)
The purpose of this study is to obtain a first insight of blood physics behaviour through a bypass graft. The paper describes a numerical analysis by the finite element method of steady blood flow through an idealized bypass graft around a stenosed artery. In this study the biochemical and mechanical interactions between blood and vascular tissue are neglected and no-slip boundary conditions including the graft are considered. Results are visualized for a better understanding of the flow characteristics such as distributions of the flow pattern, stagnation flow and recirculation zones. The outcomes will contribute to characterize the physiology of bypass grafts in the human circulatory system.